1997
DOI: 10.1016/s0169-5983(97)00018-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of splitter plate on the reverse flow in a channel

Abstract: Reverse flow inside a parallel plate channel can be achieved by placing an obstruction at the entry. The present work is carried out to study the influence of (i) splitter plates behind the flat plate obstruction at the front end and (ii) splitter plates placed at the rear end of the channel in tandem with the obstruction at the front. The results show that the splitter plate at the front end has a slight unfavourable effect due to a little reduction in the reverse flow. However, when the splitter plate is pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Tulapurkara et al (1994) have reported the in uence of the width of the obstruction relative to the test channel width and also when obstructions are placed both at the front and the rear ends of the test channel. Further, Gowda et al (1997) studied the in uence of a splitter plate at front and rear ends on the reverse ow phenomenon. The aim of the aforesaid studies was basically to increase the magnitude of the reverse ow.…”
mentioning
confidence: 99%
“…Tulapurkara et al (1994) have reported the in uence of the width of the obstruction relative to the test channel width and also when obstructions are placed both at the front and the rear ends of the test channel. Further, Gowda et al (1997) studied the in uence of a splitter plate at front and rear ends on the reverse ow phenomenon. The aim of the aforesaid studies was basically to increase the magnitude of the reverse ow.…”
mentioning
confidence: 99%
“…In subsequent studies, various facets of the phenomenon like the influence of the geometry of the obstruction (Gowda et al, 1993), the effect of obstructions placed both at the entry and the rear of the test channel (Tulapurkara et al, 1994), and the influence of splitter plates (Gowda et al, 1997) were investigated. In subsequent studies, various facets of the phenomenon like the influence of the geometry of the obstruction (Gowda et al, 1993), the effect of obstructions placed both at the entry and the rear of the test channel (Tulapurkara et al, 1994), and the influence of splitter plates (Gowda et al, 1997) were investigated.…”
Section: Figurementioning
confidence: 99%
“…Using semicircular scoops at the rear end and a flat plate at the front end, a maximum reverse flow of 83% of the free stream velocity was achieved. Gowda et al [5] investigated the influence of splitter plates a) when placed at the front end and b) when placed at the rear end. For the latter, a maximum reverse flow of 37% of the free stream velocity was obtained.…”
Section: Introductionmentioning
confidence: 99%